In Vitro Biomechanical Evaluation of the Use of Conventional and Locking Miniplate/Screw Systems for Sagittal Split Ramus Osteotomy - Ribeiro-Junior, Paulo Domingos; Magro-Filho, Osvaldo [UNESP]; Shastri, Kalpakam A.; Papageorge, Maria B. (W B Saunders Co-elsevier Inc, 2010)
Purpose: The aim of this in vitro study was to assess the biomechanical stability of 9 different osteosynthesis methods after sagittal split ramus osteotomy by simulating the masticatory forces and using a 3-point biomechanical test method.Materials and Methods: Forty-five polyurethane hemimandibles with bone-like consistency were randomly assigned to 9 groups (n = 5) and subjected to sagittal split ramus osteotomy. After 4-mm advancement of the distal segment, the bone segments were fixed by different osteosynthesis methods using 2.0-mm miniplate/screw systems: group A, one 4-hole conventional straight miniplate; group B, one 4-hole locking straight miniplate; group C, one 4-hole conventional miniplate and one bicortical screw; group D, one 4-hole locking miniplate and 1 bicortical screw; group E, one 6-hole conventional straight miniplate; group F, one 6-hole locking straight miniplate; group (3: two 4-hole conventional straight miniplates; group H. two 4-hole locking straight miniplates; and group 1, 3 bicortical screws in an inverted-L. pattern. All models were mounted on a base especially constructed for this purpose. Using a 3-point biomechanical test model, the hemimandibles were loaded in compressive strength in an Instron machine (Norwood, MA) until a 3-mm displacement occurred between segments vertically or horizontally. Data were analyzed by analysis of variance and Tukey test (alpha = 1%).Results: The multiparametric comparison of the groups showed a statistically significant difference (P<.01) between groups that used 2 miniplates (groups G and H), 1 miniplate and 1 bicortical screw (groups C and D), and only bicortical screws (group D compared with groups that used only 1 miniplate with 2 screws per segment (groups A and B) and 3 screws per segment (groups E and F).Conclusion: The placement of 2.0-mm-diameter bicortical screws in the retromolar region, associated or not with conventional and locking miniplates with monocortical screws, promoted a better stabilization of bone segments. Locking miniplates presented a better performance in bone fixation in all groups. (C) 2010 American Association of Oral and Maxillofacial Surgeons J Oral Maxillofac Surg 68:724-730, 2010